Seasonal- and event-scale variations in upwelling, enrichment and primary productivity in the eastern Great Australian Bight. (November 2018) - van Ruth, Paul D.; Patten, Nicole L.; Doubell, Mark J.; Chapman, Piers; Rodriguez, Ana Redondo; Middleton, John F.
Abstract: We used a suite of physical, chemical and biological datasets to assess the influence of upwelling/downwelling on enrichment and primary productivity in shelf waters of the eastern Great Australian Bight at seasonal and event scales. Results showed that the length of an upwelling season did not dictate its intensity or productivity, and that long seasons were not necessarily the most intense or productive. At the event scale, temperature and salinity were found to be better indicators of enrichment of shelf waters than wind stress, with temperatures < 15 °C and salinities < 35.6 psu associated with elevated concentrations of NOx (> 2 µm) and bursts of primary productivity (up to ∼ 700 mg C m −2 d −1 ). A key finding of this study was the importance of differentiating between upwelling events and enrichment events. The former occurred in the early upwelling season (November-December) and were demonstrated by periods of positive wind stress. The latter only occurred in the late upwelling season (January – April), and saw water with temperatures < 15 °C and salinities < 35.6 psu drawn onto the shelf and into the euphotic zone where it was available for primary producers. We used this information to develop a conceptual model which describes five different meteorological/oceanographic scenarios that occur in the eastern GAB, and their potential influence on enrichment and primary productivity, and hypothesise that total ecosystem productivity depends on the combination of these scenarios that occurs in the region in a given season/year. It is our contention that the early upwelling season represents a preconditioning period that plays a critical role in characterising late season enrichment events, and drives overall seasonal productivity.